The Impact of the Governor's Consultation and Consideration on Central Government Administrative Policy in Aceh - Prang, Amrizal J.; Nasir, Muhammad; Arnita, Arnita; Sriwahyuni, Yeni (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The Central Government's administrative policies relevant to the Aceh Government are executed subsequent to consultation and deliberation with the Governor, as specified in Article 8, paragraph (3) of Law Number 11 of 2006 about the Aceh Government (UUPA). This encompasses issues such as geographical delineation, the formation of designated zones, and the formulation and enactment of statutes and regulations pertinent to the Aceh Government. This authority contrasts with the distinct and exceptional position of the Provinces of Papua and West Papua, the Province of the Special Region of Yogyakarta, and the Regional Government together. This study seeks to evaluate the efficacy of the Governor's authority in consultation and deliberation of the administrative policies of the Central Government in Aceh. Aceh, acknowledged for its distinctive autonomy status, holds distinct jurisdiction in the execution of governmental administrative responsibilities. This is qualitative research, in which method of data collection includes in-depth semi-structured interviews and document analysis. The findings demonstrate that the Governor's capacity to engage and deliberate is essential for aligning central policies with local needs. However, other problems hinder the execution, including inadequate coordination among agencies and differing interpretations of rules between the Central Government and the Aceh Government. Moreover, there is little oversight by the Aceh Special Autonomy Monitoring Team from the DPR-RI, coupled with an absence of penalties for delays in the execution of the UUPA. For effective execution, it is imperative that both the Central Government and the Aceh Government exhibit political will and consistency. The collaboration between the Central Government and the Aceh Government Consultation Teams should transform into an Ad-Hoc Team to promote a mutual understanding and provide continuous oversight of the implementation process.